Overview Of Visitors' Knowledge About Dengue Fever (Dhf) Prevention Efforts: A Study At Dr. Iskak Tulungagung Regional Hospital - Riza Yuliawati; Adevia Salma; Alviyah Musayadah; Dominggus Mone; Ernesta Tamo Ina; Muhammad Fikri Haikal; Indriani Setiyowati (Universitas STRADA Indonesia, 2026)
Dengue Hemorrhagic Fever (DHF) remains a significant public health problem in Indonesia. It is caused by the dengue virus transmitted through Aedes aegypti and Aedes albopictus mosquito bites. Based on data from Dr. Iskak General Hospital Tulungagung, DHF ranks as the third leading cause of hospitalization, indicating low public awareness regarding prevention. This research used a quantitative descriptive survey design involving 25 respondents, consisting of 12 males and 13 females. Data were collected through observation, interviews, and questionnaires containing 10 positive and negative statements using a three-point Likert scale. The data were analyzed descriptively to determine frequency and percentage distributions of knowledge levels regarding DHF prevention. The results showed that 72% of respondents had good knowledge, 20% had fair knowledge, and 8% had poor knowledge, with an average score of 27.8 out of 30. Most respondents understood the causes, transmission, and preventive measures of DHF, including the 3M Plus movement. Factors such as age, education, and exposure to health education activities influenced knowledge levels. These findings support previous studies stating that health education significantly improves community awareness and preventive behavior. Health education and survey activities effectively enhance public knowledge about DHF prevention. Continuous education and interactive communication media are recommended to improve community awareness and reduce DHF incidence.